2017
DOI: 10.1002/acr.23005
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extensor Strength and Risk of Structural, Symptomatic, and Functional Decline in Knee Osteoarthritis: A Systematic Review and Meta‐Analysis

Abstract: Meta-analysis showed that lower knee extensor strength is associated with an increased risk of symptomatic and functional deterioration, but not tibiofemoral JSN. The risk of patellofemoral deterioration in the presence of knee extensor strength deficits is inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
118
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 42 publications
5
118
0
2
Order By: Relevance
“…16 We chose to distinguish between high and low quality in line with another similar article, with a cut-off score of >60%, which in this case was a score of >8. 18 The results are only valid for this systematic review, and should not be directly transferred to other contexts, or interpreted as the truth.…”
Section: Methodological Quality Assessmentmentioning
confidence: 86%
See 1 more Smart Citation
“…16 We chose to distinguish between high and low quality in line with another similar article, with a cut-off score of >60%, which in this case was a score of >8. 18 The results are only valid for this systematic review, and should not be directly transferred to other contexts, or interpreted as the truth.…”
Section: Methodological Quality Assessmentmentioning
confidence: 86%
“…Studies with a score ≥8 (>60% of the maximal attainable score) were classified as high quality according to another systematic review from our group. 18 Two authors scored the studies independently, and then the scores were compared (MML and LE; MML and KS; MML and MAR). In cases of disagreement, the authors tried to achieve consensus.…”
Section: Study Methodological Quality Assessmentmentioning
confidence: 99%
“…Knee extensor weakness is a typical feature of knee OA 13,14 , and is associated with the development of symptomatic knee OA 15 as well as functional decline over time in people with knee OA 16 . Evidence from observational 17,18 and preepost exercise studies 19e22 reports associations between change in knee extensor muscle strength and change in pain 20e22 and self-reported physical function 17e20 in people with knee OA 17e22 or at risk for knee OA 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of individuals with knee osteoarthritis (OA) and those at risk of OA have shown that quadriceps weakness is strongly associated with functional limitations . For these individuals, addressing quadriceps strength often becomes a major target of rehabilitation interventions, including general aerobic and local strengthening exercises, with the hope of improving physical function, reducing pain and physical disability, and avoiding further progression of OA .
We explored quadriceps strength and physical function in individuals with knee osteoarthritis from the Multicenter Osteoarthritis Study. We found evidence of strength thresholds for functional tasks that involve the body acting against gravity, such as walking or rising from a chair, in women but not in men. These thresholds in strength may provide a means of identifying individuals at the brink of disability, for whom increments in strength may be associated with improvements in physical function or greater ease in carrying out common tasks in daily life; for individuals above the strength threshold, focus should be on maintaining strength.
…”
Section: Introductionmentioning
confidence: 99%